2013
DOI: 10.1111/fwb.12175
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope evidence indicates the incorporation into Japanese catchments of marine‐derived nutrients transported by spawning Pacific Salmon

Abstract: Summary Pacific salmon (Oncorhynchus spp.) transport marine‐derived nutrients (MDN) and organic matter to freshwater ecosystems, which enhances the productivity of North Pacific ecosystems. Relatively few studies, however, have evaluated the MDN subsidy to both the aquatic system and the terrestrial catchment simultaneously. Using stable isotope analysis, we tested how the dynamics of MDN differed between the river and adjacent riparian forest in rivers of the Shiretoko World Natural Heritage Site in eastern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 68 publications
2
28
1
Order By: Relevance
“…This is in line with findings in Canadian seabird colonies [12,21] and relationships observed between d 15 N of terrestrial vegetation and distance to a salmon stream [7,37] or relative salmon carcass density [37]. (c) Potential drivers of changes in freshwater ecosystems along a gradient of bird impact…”
supporting
confidence: 88%
See 1 more Smart Citation
“…This is in line with findings in Canadian seabird colonies [12,21] and relationships observed between d 15 N of terrestrial vegetation and distance to a salmon stream [7,37] or relative salmon carcass density [37]. (c) Potential drivers of changes in freshwater ecosystems along a gradient of bird impact…”
supporting
confidence: 88%
“…The use of d 15 N as an indicator of MDN input has been supported in diverse studies (e.g. [7,12,21,37]). Details of the models used to test the relationships are provided in electronic supplementary material, Methods S1.…”
mentioning
confidence: 99%
“…Overwinter monitoring of biofilm isotopes following mitigation treatment could help determine which mechanism of biofilm turnover is most important. In streams with natural spawning runs and long-term delivery of marine-derived nutrients, legacy effects on d 15 N and d 13 C of biofilms have been reported (Reisinger et al 2013), and could possibly manifest in response to nutrient additions over longer timescales if those nutrients were moved into long-term storage pools like riparian soils and vegetation (Naiman et al 2002, Koshino et al 2013.…”
Section: Discussionmentioning
confidence: 99%
“…bears, pine marten, cougar, and wolverine) travel among patched habitats following environmental cues to time the seasonal arrival of peak food "rain" [88,89]. A suitable example of large mammal predators influencing nutrient dynamics along riparian zones is bears with their salmon prey (marine-derived nutrients, MDN) [84,90]. Quinn et al (2009) reported that 49% of chum (Oncorhynchus keta) and pink (Oncorhynchus gorbuscha) salmon captured by bears (genus Ursus L., 1758) were carried into the riparian forests in southeastern Alaska [91].…”
Section: Impacts Of Aquatic Resource Subsidies On Specific Terrestriamentioning
confidence: 99%